2008
DOI: 10.1007/s00394-008-0727-6
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity and their relation to dietary habits and socio-demographic characteristics among male primary school children in Al-Hassa, Kingdom of Saudi Arabia

Abstract: The prevalence of childhood obesity is escalating and approaching figures reported in the developed countries. Less healthy dietary habits and poor food choices may be responsible for this high prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
113
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 27 publications
18
113
4
1
Order By: Relevance
“…Results presented here showed that socio-economic status had an effect on rates of OW and OB, which agreed with those of Amin et al [8] and Al-Hazzaa et al [19]. On the other hand, our results are inconsistent with Katzmarzyk [21] who cited that Canadian children from low income families have higher rates of OW compared to their counterparts in high income families.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Results presented here showed that socio-economic status had an effect on rates of OW and OB, which agreed with those of Amin et al [8] and Al-Hazzaa et al [19]. On the other hand, our results are inconsistent with Katzmarzyk [21] who cited that Canadian children from low income families have higher rates of OW compared to their counterparts in high income families.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, 16.5% of school girls in Riyadh skipped their breakfast [26]. Amin et al [8] indicated that 47.8% of obese and overweight male primary schoolchildren in Al-Hassa (KSA) skipped their breakfast. Farghly et al [11] found that 28% of schoolchildren in Abha area skipped their breakfast, and it was more alarming as 17% of female high school students never ate breakfast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total number of responses bottled milk and carbonated drinks in bottles [14,[17][18][19]. Wyne et al reported that carbonated drinking items are popular and give these contents in feeding bottles to the children [15].…”
Section: Introductionmentioning
confidence: 99%
“…Wyne et al reported that carbonated drinking items are popular and give these contents in feeding bottles to the children [15]. Several studies have corroborated these findings, with some suggesting that as many as seventy five percentages of the Saudi children took soft drinks and fruit juices in feeding bottle [17][18][19]. The consumption of sugar containing drinks has also been reported in older children.…”
Section: Introductionmentioning
confidence: 99%